Visualizing genomes: Techniques and challenges - Nielsen, C.B.; Cantor, M.; Dubchak, I.; Gordon, D.; Wang, T.
As our ability to generate sequencing data continues to increase, data analysis is replacing data generation as the rate-limiting step in genomics studies. Here we provide a guide to genomic data visualization tools that facilitate analysis tasks by enabling researchers to explore, interpret and manipulate their data, and in some cases perform on-the-fly computations. We will discuss graphical methods designed for the analysis of de novo sequencing assemblies and read alignments, genome browsing, and comparative genomics, highlighting the strengths and limitations of these approaches and the challenges ahead. © 2010 Nature America, Inc. All rights reserved.
Keywords: CHROMATIN ASSEMBLY AND DISASSEMBLY; COMPARATIVE GENE MAPPING; COMPARATIVE GENOMIC HYBRIDIZATION; COMPUTER AIDED DESIGN; COMPUTER PROGRAM; DATA ANALYSIS; GENE EXPRESSION; GENE SEQUENCE; GENETIC CONSERVATION; GENETIC DATABASE; GENETIC IDENTIFICATION; GENETIC VARIABILITY; GENOMICS; GENOTYPE; HIGH THROUGHPUT SCREENING; HIGH THROUGHPUT SCREENING; PRIORITY JOURNAL; SEQUENCE ALIGNMENT; SEQUENCE ANALYSIS; SYNTENY; TRANSCRIPTION REGULATION